Bacterial infiltration comparison of two root canal filling techniques - Gislaine Pontarollo; Raphael Hamerschmitt; Beatriz Coelho; Denise Piotto Leonardi; Flávia Sens Fagundes Tomazinho (Revista Sul-Brasileira de Odontologia, 2015)
Root canal system filling aims to the hermetic sealing of the space formerly occupied by the dental pulp. Objective: The aim of this study was to analyze the bacterial infiltration of Enterococcus faecalis in root canals filled through two techniques: single cone technique (group A) and thermoplasticized gutta-percha technique (group B). Material and methods: A total of 40 single-rooted human premolars were divided into two experimental groups (n = 15) and two control groups: positive (n = 5) and negative (n = 5). The root canals were prepared with ProTaper Universal system up to size F3 file and filled with the corresponding gutta-percha point. Teeth were mounted on a dual-chamber model, where the infiltration of E. faecalis was evaluated for a 30-day period by BHI turbidity indicating bacterial growth. Results: After the trial period all specimens in experimental and positive control groups showed turbidity of the culture medium. The average number of days until culture medium turbidity was 11.42 days for group A, 16.69 days for group B, and 5.5 days for positive control. By applying Anova test, there was no statistically significant difference between groups (p > 0.05). This allowed the observation that no difference between the obturation techniques in the infiltration of E. faecalis could be observed by the methodology used. Conclusion: It can be concluded that regardless of the obturation techniques, bacterial infiltration occurred.